2012
DOI: 10.1227/neu.0b013e31822d9749
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serial Intraoperative Surgical Microscope-Integrated Intraoperative Near-Infrared Indocyanine Green Videoangiography in Patients With Cerebral Arteriovenous Malformations

Abstract: We found that ICG videoangiography is helpful for resecting cerebral arteriovenous malformation. It is especially effective in visualizing the nidus and superficial drainers, as well as changes in flow after clipping or coagulating of feeders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 10 publications
1
42
0
1
Order By: Relevance
“…Thanks to its quickness and noninvasiveness and providing real-time information it has become an invaluable tool to intraoperative surgical decision-making and it has been widely proved that its accuracy can be totally compared to intraoperative DSA or microdoppler [25,28]. Potential applications in vascular neurosurgery have significantly broadened over time; in addition, recent experiences have shown ICG-VA potential use in a very different set neurosurgical branches, including oncological surgery, endocscopy, pituitary, cerebral hemodynamic studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thanks to its quickness and noninvasiveness and providing real-time information it has become an invaluable tool to intraoperative surgical decision-making and it has been widely proved that its accuracy can be totally compared to intraoperative DSA or microdoppler [25,28]. Potential applications in vascular neurosurgery have significantly broadened over time; in addition, recent experiences have shown ICG-VA potential use in a very different set neurosurgical branches, including oncological surgery, endocscopy, pituitary, cerebral hemodynamic studies.…”
Section: Discussionmentioning
confidence: 99%
“…7 articles have been published about ICG and AVMs [23][24][25][26][27][28][29], the first one was by Takagi et al [28] …”
Section: Vascular -Avmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports have suggested that ICG-VAG is a useful guiding tool during the surgical treatment of AVM (48). However, to the best of our knowledge, there are no reports on intraoperative ICG-VAG performed to confirm SRAVMs.…”
Section: Indocyanine Green Videoangiographymentioning
confidence: 96%
“…3). Следует подчеркнуть, что данная технология позво-ляет достаточно надежно идентифицировать оста-точные узлы мальформации [8,13]. По нашему мне-нию, это становится особенно актуально при удале-нии мальформаций после их эмболизации клеевы-ми и не клеевыми материалами (рис.…”
Section: возможности и ограничения ицз ваunclassified